Status of ant research and species first described from Nepal with new distribution records - Subedi, Indra Prasad; Budha, Prem Bahadur (Journal of Natural History Museum, 2020)
Nepal occupies the Central part of the Himalayas and offers unique ecological and species diversity. Ants are amongst the most diverse and successful insects on the Earth. Study of Nepalese myrmeco-fauna has started only after 1906 and little is known about them except the availability of few published works only. This paper provides a brief overview of the status of ant research in Nepal, type localities, distribution records, diagnosis and etymology of ant species which are described for the first time from Nepalese specimens. All the type materials of these species are deposited in museums abroad and it seems essential to deposit voucher specimens in the country to excel taxonomic work on Nepalese fauna. Systematic surveys of ants and well-curetted ant depository will facilitate the discovery of more ant species from Nepal. We hope that this paper will stimulate local interest in the study of ants of Nepal.